Endoscopic treatment can be a viable therapeutic option for esophageal gastrointestinal stromal tumors. (4th March 2022) - Du, Haojie; Ning, Longgui; Chen, Hongtan; Hu, Fengling; Shan, Guodong; Chen, Wenguo; Xu, Guoqiang
Abstract: Background: Esophageal gastrointestinal stromal tumors(GISTs) are extremely rare. We sought to determine whether endoscopic treatment can be a viable therapeutic option for esophageal GISTs. Methods: A total of 20 cases with histological diagnosis of esophageal GISTs were obtained from our center between 2008 and 2020. Data on the clinicopathological features and treatment were recorded. Results: There were 9 males (45%) and 11 females (55%) in this study, with a median age of 56 years. The tumors preferentially occurred in the middle and lower parts of the thoracic esophagus (45 and 40%, respectively). The mean size of the tumors was 2.27 cm and mitotic index was no more than 5/50 high power field (HPF) in all patients. In this study, 11 patients received endoscopic treatment and nine patients underwent surgical resection. Tumors ranged from 0.6 to 4 cm in the endoscopic treatment patients and 0.5 to 7 cm in the surgical patients. There were no significant differences in gender, age, symptoms, tumor location, tumor size, mitotic index, and adjuvant imatinib therapy between the endoscopic treatment group and the surgery group (all p > .05). The Kaplan-Meier curve suggested that there was also no significant difference in disease-free survival between the two groups ( p = .264). Conclusions: Endoscopic treatment may be an option for the treatment of esophageal GISTs smaller than 5 cm with a mitotic index no more than 5/50 HPF.